Abstract of a paper on "Railway reform" - Gibson, Edward (Statistical and Social Inquiry Society of Ireland, 1865)
The paper was intended to show the powers vested in the nation of purchasing up the railways of the United Kingdom constructed since 1844, and the arguments which have been advanced to induce the public to exercise those powers.
Railway reform
Read, Tuesday, 17th January, 1865
Keywords: British railway reform; Nationalisation of British railways; 314.15